Linear periodization of strength training in blocks attenuates hypertension and diastolic dysfunction with normalization of myocardial collagen content in spontaneously hypertensive rats. Issue 1 (January 2020) - Perilhão, Mauro S.; Krause Neto, Walter; da Silva, Ariana A.; Alves, Lílian l.S.; Antonio, Ednei L.; Medeiros, Alessandra; Rica, Roberta Luksevicius; Serra, Andrey J.; Tucci, Paulo J.F.; Bocalini, Danilo S.
Abstract : Background and method: This study evaluated the effects of a linear block strength training programme on the parameters of cardiac remodelling in spontaneously hypertensive rats. Thirty-nine rats were equally distributed in four groups: normotensive sedentary, normotensive trained, hypertensive sedentary and hypertensive trained. The strength training protocol was organized in three mesocycles of 4 weeks, with an increase in the training load organized in a linear fashion for each block, considering the weight established in the maximum loaded load test. The following parameters were evaluated: ventricular function assessed by echocardiogram, caudal blood pressure, ventricular haemodynamics and cardiac masses. Two-way analysis of variance was used to determine the differences between the group and time. Results: After 12 weeks of training, the hypertensive trained group presented the following results: increased muscle strength, reduced blood pressure, reduced heart rate, isovolumetric relaxation time and total collagen content, with increased cardiac function, without promoting changes in the mass and nuclear volume of cardiomyocytes. Also, blood pressure reduction seems to be associated with both muscle strength adjustments and total load progress. Conclusion: The findings of this study showed that the training programme carried out attenuated systemic arterial pressure and preserved the ventricular function of spontaneously hypertensive rats without cardiac mass change.